PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING DENGAN MEDIA VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR IPA SISWA KELAS V SDN 9 AMPENAN TAHUN PELAJARAN 2019/2020 - Lalu Irwan Ansori; Abdul Kadir Jaelani; Lalu Hamdian Affandi (PROGRES PENDIDIKAN, 2020)
This study aims to determine the effect of the Contextual Teaching and Learning model with instructional video media on the learning outcomes of Natural Sciences fifth-grade students at SDN 9 Ampenan in the 2019/2020 Academic Year. This type of research is an experimental research design with a Quasi-Experimental type Nonequivalent Control Group Design. The population of this research was all students of class V SDN 9 Ampenan consisting of classes V/A, V/B, and V/C totaling 93 students. The sampling technique in this study was purposive sampling with a sample of 61 students. Data collection methods are observation, test, and documentation. Data analysis was performed with a normality test, a homogeneity test, and a hypothesis test using the Independent Sample T-test formula. Based on the post-test results obtained the average value of science learning outcomes of students in the experimental class of 83.28 while the average value in the control class was 77.76. So the average experimental class is higher than the control class. Hypothesis testing at a significant level of 5% yields a t-value of 2,140 and a table of 2,000. Based on the test criteria if tcount > ttable (2,140 > 2,000), then H0 is rejected and Ha is accepted. Therefore, it can be concluded that there is an effect of the Contextual Teaching and Learning model with instructional video media on the learning outcomes of the fifth-grade students of SDN 9 Ampenan in the 2019/2020 Academic Year.